Country Procurement Assessment Report : Mauritius, Volume 1 - World Bank (Washington, DC, 2013)
The purpose of the Country Procurement Assessment Report (CPAR) is to assess (a) the efficiency, economy and transparency of the public procurement system; (b) commercial practices in the private sector, particularly in relation to imports, and, (c) the institutional capacity of entities dealing with procurement in the country. Mauritius has made credible efforts to provide a framework of transparency, and accountability; it has strong institutional capacity; a checks and balances system is in place; its audit system is working, and the country is firmly committed to provide a transparent climate for, and information on public spending to the general public. The recommended improvements are in line with the already initiated Government program. The main recommendations address the need to: (1) develop a legal framework on procurement procedures, and regulations; (2) standardize, and computerize the procurement documentation, e.g. the bidding documents; (3) strengthen the regulatory role of the Central Tender Board (CTB); (4) provide training for public procurement staff in ministerial departments; (5) integrate the ex-post review of procurement compliance in auditing practices; (6) streamline, and simplify import procedures; and, (7) review the economic performance, and quality of imports carried out by the private sector, and/or parastatal entities. Volume I, the main report, identifies relevant country information on procurement, and discusses the analysis of findings. Volume II, attachments and annexes, discusses each of the major issues in depth, i.e., public and private sector procurement practices.